PENGARUH DUKUNGAN TEMAN SEBAYA TERHADAP POLA PIKIR BERWIRAUSAHA PADA PELAKU USAHA MUDA DI KOTA BONTANG - Irianto; Sa'ad, Muhammad Ibnu (Manajemen Pendidikan Program Doktor, 2023)
Youth entrepreneurship has a signiﬁcant impact on productivity, economic growth and the creation of new technologies. Peer support, entrepreneurship education, and self-eﬃcacy have been shown to inﬂuence students' entrepreneurial intentions.Social support from family and peer environment is also related to entrepreneurial intention. In addition, research also shows thatpeers have a signiﬁcant inﬂuence on entrepreneurial career choice, even greater than the inﬂuence of parents. Therefore, it can be concluded that peer support plays a signiﬁcant role in the development of an entrepreneurial mindset in young entrepreneurs. Thisshows the importance of paying attention to social environmental factors, such as peer support, in an eﬀort to develop anentrepreneurial spirit in the younger generation.